DNA nanostructure‐encoded fluorescent barcodes. Issue 1 (29th December 2020) - Zhai, Tingting; Li, Qian; Shen, Jianlei; Li, Jiang; Fan, Chunhai
Abstract: Identification and differentiation of various bioanalytes with high spatial and temporal resolution have spawned fluorescent barcode‐based detection and imaging. DNA nanostructures with excellent structure programmability, addressability, and near‐atomic structure accuracy have emerged as a versatile platform to develop fluorescent barcodes through finely controlled dye numbers, relative distances, and compositions. A variety of DNA fluorescent barcodes with distinguishable spectral colors, geometries and digitized fluorescence intensities have been constructed and favorably implemented in the field of bioimaging, multiplex bioassay, and information security. In this review, we first summarize the state of the art of self‐assembled DNA nanostructures. Next, the utilization of DNA nanostructure to develop fluorescent barcodes and the photophysical properties of DNA‐templated fluorophores are reviewed. Finally, the applications of DNA fluorescent barcodes for biosensing and imaging, and the challenges and outlook of DNA nanostructure‐engineered fluorescent barcodes are discussed. Abstract : DNA nanostructures have extraordinary advantages in placing fluorescent molecules with near‐atomic scale precision and controllable number. In this review, we summarize the recent progress of DNA nanostructure‐encoded fluorescent barcodes and discuss the intermolecular photophysical interactions of dyes on the DNA template. Finally, the applications of fluorescent barcodes in biosensing and bioimaging are reviewed.